2017
DOI: 10.1002/bjs.10575
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of antibiotic therapy versus appendicectomy for the treatment of uncomplicated acute appendicitis from the APPAC randomized clinical trial

Abstract: Patients receiving antibiotic therapy for uncomplicated appendicitis incurred lower costs than those who had surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
64
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 28 publications
(45 reference statements)
12
64
0
2
Order By: Relevance
“…In this cohort, already the majority of cases (64%) was treated in general hospitals and, assuming equivalent outcomes, this may be further encouraged. Non-operative treatment of appendicitis has also been proposed to be an economical choice [17], at no compromise in safety according to several recent studies [11,49,50]. Patients treated non-operatively were excluded from this study, and the DBC reimbursement system does not allow for discrimination of operating costs from admission day costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort, already the majority of cases (64%) was treated in general hospitals and, assuming equivalent outcomes, this may be further encouraged. Non-operative treatment of appendicitis has also been proposed to be an economical choice [17], at no compromise in safety according to several recent studies [11,49,50]. Patients treated non-operatively were excluded from this study, and the DBC reimbursement system does not allow for discrimination of operating costs from admission day costs.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from avoiding surgery and its potential complications, non-operative treatment might also be beneficial in terms of healthcare cost savings. However, the available evidence is ambiguous [15][16][17][18]. Regarding the choice of operative approach, most studies have demonstrated comparable or better clinical outcomes for minimally invasive compared to open appendectomy, however at higher medical care costs [19][20][21][22].…”
mentioning
confidence: 99%
“…Approximately 25% of acute appendicitis cases present as complicated acute appendicitis [33]. Increasing evidence from randomized trials suggests that the majority of patients with uncomplicated acute appendicitis can be treated safely with antibiotics with low tumor rates avoiding unnecessary surgery resulting in decreased morbidity and cost savings [1,3,6]. The markedly lower tumor rate associated with uncomplicated acute appendicitis is of vital clinical importance as non-operative management of uncomplicated appendicitis is one its way of becoming one of the treatment options for uncomplicated acute appendicitis [1,3,34] as the appendiceal tumors are not generally suspected preoperatively [30,35].…”
Section: Discussionmentioning
confidence: 99%
“…Uncomplicated acute appendicitis may also resolve spontaneously without even antibiotics, let alone surgery [5]. Non-operative management of uncomplicated acute appendicitis has also been shown to reduce treatment costs [6]. In cases of complicated acute appendicitis with a formation of a circumscribed abscess, the need for interval appendectomy after initial successful conservative treatment has also been questioned as the risk of appendicitis recurrence is quite low between 5 and 20% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Gold standard treatment of acute appendicitis is the appendectomy. Today, after the development and popularization of laparoscopic interventions, appendectomy has become the preferred method in the treatment of acute appendicitis.However, appendectomy, whether open or laparoscopic, poses many risks in terms of surgery and anesthesia, like as all other surgical procedures, leading to costs, resulting in complications at certain rates [3][4][5]. In thepresent study, which is planned without criticizing the valuable place of appendectomy in the treatment of patients with acute appendicitis, it was aimed to investigate whether antibiotherapy can be preferred to the emergency surgical International Journal of Medical Science and Clinical Invention, vol.…”
Section: Introductionmentioning
confidence: 99%